Hubungan Faktor Penularan dengan Kejadian Malaria pada Pekerja Migrasi yang Berasal dari Kecamatan Lengkong Kabupaten Sukabumi - Marliah Santi; Lukman Hakim (Loka Litbang Kesehatan Pangandaran, 2011)
Abstract. Lengkong sub-district is malaria-endemic areas with a high morbidity. In the pastthree years, there is a decrease in the number of malaria cases, but the number of importedmalaria cases has increased significantly from the migration of workers returning from malaria-endemic areas outside Java. Epidemiological studies have been conducted with theaim of knowing the transmission factors associated with malaria incidence in the populationof Lengkong, Sukabumi who ever migrated. Research conducted in the Cilangkap andLangkapjaya Village held in November 2011. The type of research is quantitative with across-sectional study design. The study population is the all of community that perform migratein 2011 and at the time of the study was in the villages. The data was collected by interviewingwith respondents about the destination of migration, length of stay in the area ofmigration, the use of chemoprophylaxis before leaving for migration, history of malaria atbefore, the health seeking, installation of wire netting on ventilation of house, the use of bednets, and also the incidence of malaria as long as migration and at period of one month afterdischarge. The collected data is analyzed to determine relationship of each independent variablewith the dependent variable. The results obtained from 100 respondents, 97% migrationto malaria-endemic areas, length of stay was 96% in > 1 month, 55% did not use chemoprophylaxis,57% had been sick with malaria at before, 69% seeking health to non healthofficer, 100% did not use bed nets, and house without wire netting, and also 26% had beenexposed wit malaria. Bivariate analysis shows, the use of chemoprophylaxis, previous historyof malaria and sought health treatment are factor associated with the incidence of malariaon labor migration.